2003
DOI: 10.1007/bf02983247
|View full text |Cite
|
Sign up to set email alerts
|

Racial background is a determinant factor in the maintenance dosage of Warfarin

Abstract: Warfarin is a drug commonly used in the prevention of thromboembolic events. There have been reports suggesting that racial background may influence warfarin dose requirements. Malaysia is a multiracial country in which there are 3 major races, Malay, Chinese, and Indian. We examined 100 patients from our hospital on stable maintenance doses of warfarin, with international normalized ratio (INR) of 2.0 to 3.5. We found that the mean warfarin dose for Indian patients (n = 19) was 6.9 mg, for Chinese patients (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…5, 9 Moreover, it has been reported that compared with Europeans, the incidence of thromboembolism is low in Japan, despite the less intensive regimen; 10,11 which indicates that adjusted low-dose warfarin (eg, PT-INR 1.6-2.6) is optimal for prevention of thromboembolism in Japanese patients. 12, 13 Considering these racial differences in the anticoagulation therapy, we attempted to validate the IWPC pharmacogenetic dose algorithm for warfarin in Japanese patients under low-TAKEUCHI F et al…”
Section: Editorial P 850mentioning
confidence: 99%
“…5, 9 Moreover, it has been reported that compared with Europeans, the incidence of thromboembolism is low in Japan, despite the less intensive regimen; 10,11 which indicates that adjusted low-dose warfarin (eg, PT-INR 1.6-2.6) is optimal for prevention of thromboembolism in Japanese patients. 12, 13 Considering these racial differences in the anticoagulation therapy, we attempted to validate the IWPC pharmacogenetic dose algorithm for warfarin in Japanese patients under low-TAKEUCHI F et al…”
Section: Editorial P 850mentioning
confidence: 99%
“…We hypothesize that Asp36Tyr may be relevant to other population groups of whom warfarin resistance is characteristic, such as Indians. 7 The issue of incompatibility of present knowledge with prediction of warfarin dose response in patients of African origin has been raised in several recent studies. [8][9][10] It has been suggested that African ethnic groups For personal use only.…”
Section: Vkorc1 Asp36tyr Warfarin Resistance Marker Is Common In Ethimentioning
confidence: 99%
“…[14][15][16] Ethnic stratification of the known CYP2C9 and VKORC1 genetic variants provides only partial explanation of these differences. 10,[17][18][19][20][21][22] The major limitation of this study is the small number of patients and its cross-sectional nature.…”
Section: Asp36tyr and Vkorc1 Haplotypesmentioning
confidence: 99%